Real-time polymerase chain reaction (PCR) cycle threshold and Clostridioides difficile infection outcomes - Choi, Byungwoo; Wong, Ken Koon; Dunn, Aaron N.; Butler, Robert; Fraser, Thomas G.; Procop, Gary W.; Richter, Sandra S.; Isada, Carlos M.; Deshpande, Abhishek (Infection control and hospital epidemiology, 2021)
Clostridioides difficile infection (CDI) causes significant morbidity and mortality; however, the diagnosis of CDI remains controversial. The primary aim of our study was to evaluate the association of polymerase chain reaction (PCR) cycle threshold (Ct) values with CDI disease severity, recurrence, and mortality among adult patients with CDI. Retrospective cohort study. Single tertiary-care hospital. Adult patients diagnosed with hospital-onset, healthcare facility-associated CDI from June 2014 to September 2015. We performed a retrospective chart review of included patients. Univariate and multivariable logistic regression methods were used to evaluate the association between Ct values and CDI severity, 8-week recurrence, and 30-day mortality. Among 318 included patients, 51% were male and the mean age was 62 years; ~32% of the patients developed severe CDI and 11% developed severe-complicated CDI. The 30-day all-cause mortality rate was 11% and the 8-week recurrence rate was 9.5%. The overall mean Ct value was 32.9 (range, 23-40). Multivariable analyses showed that lower values of PCR Ct were associated with increased odds of 30-day morality (odds ratio [OR] 0.83; 95% confidence interval [CI], 0.72-0.96) but were not independently associated with CDI severity (OR, 0.99; 95% CI, 0.90-1.09) or recurrence (OR, 0.88; 95% CI, 0.77-1.00). Our findings suggest that PCR Ct values at the time of diagnosis may have a limited predictive value and utility in clinical decision making for inpatients with CDI. Larger, prospective studies across different patient populations are needed to confirm our findings.